A prospective observational study on obesity related maternal and fetal complications at government headquarters hospital, Cuddalore - Sethupathy, Raja Chella; Rathinasabapathy, Kala; Apparu, Kumar (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
Background: The magnitude of the obesity prevalence has been increasing in developed and developing nation. This study was to find out the obesity related maternal and neonatal complications in Cuddalore district. Methods: This prospective observational COHORT study was carried out among the pregnant women for whom detailed history was obtained with complete general and physical examination. They were followed up to delivery and postpartum until discharge and the outcomes were studied. Results: The mean body mass index (BMI) of obese women was 32.42 and that of control women was 22.59. Obese women had increased incidence of gestational diabetes mellitus at 2.67%, gestational hypertension in obese group at 10.67%, caesarean delivery at 85.33% and needed induction at 89.33% when compared to control group at 1.33%, 5.33%, 36% and 72% respectively. Obese mothers of caesarean delivery (8%) had a prolonged hospital stay due to wound gaping and wound infections, when compared to mothers of control group (2.67%). Babies of obese mothers (16%) had a prolonged hospital stay due to respiratory distress, neonatal jaundice and macrosomia, when compared to babies of mothers from control group (2.67%). We found that 33.33% of obese women delivered babies of weight 3.5 kg and above, when compared to control group (6.67%) and some needed NICU admission (14.67%). Conclusions: The study confirmed from the population that obesity during pregnancy has increased number of complications like gestational diabetes, gestational hypertension, increased need for cesarean section, large babies needing NICU support.